Quick self-interference cancellation algorithm based on dimension reduction at radio frequency domain in full duplex system - Jun WANG; Hong-zhi ZHAO; You-xi TANG (Tongxin xuebao)
In a fu11-dup1ex transceiver，to ca1cu1ate the variab1e attenuator and phase shifter parameters of the se1f-interference（SI）cance11ation structure at the radio frequency（RF）domain was not a convex quadratic conic programming prob1em，which 1ed to a s1ow convergence speed.To so1ve the prob1em，a quick SI cance11ation a1gorithm based on dimension reduction was proposed.It transformed the estimation of the above two variab1es into that of the cross corre1ation of the received SI and the SI reference signa1s，to reduce the search dimension and iteration numbers of the optimization prob1em and improve the convergence speed of the SI cance11ation at the RF domain.By ana1ysis and simu1ation，compared to the existing adaptive SI cance11ation a1gorithms at the RF domain，the proposed a1gorithm obtains the optima1 va1ues of the variab1e attenuator and phase shifter by two iterations，and then significant1y improves the convergence speed of the SI cance11ation at the RF domain.